the Effect of Using a Contextual-Based Physics e-Module on Improving Students' Understanding of Concepts in Class X Measurement Materials of SMAN 1 V Koto Kampung Dalam - wulandari, wulandari (PILLAR OF PHYSICS EDUCATION, 2024)
Understanding concepts is an individual's ability to understand the meaning of concepts, situations and facts that they know. Class X students' understanding of concepts at SMA Negeri 1 Kampung Dalam needs attention, because students' conceptual understanding is still relatively low. This is because the learning that has been developed has not been adapted to students' needs, namely teaching materials, resulting in student learning outcomes not reaching the expected results. One of the teaching materials that can improve students' understanding of physics learning material is E-Module. This research aims to determine the effect of using the Contextually Based Physics E-Module on Students' Understanding of Concepts. To achieve the goal, the Quasi Experiment method was applied with a Posttest-Only Control Design. The data in this research is in the form of students' understanding of the measurement material, collected through a test instrument, which consists of 7 indicators and is translated into 30 questions. Data analysis used the T test at a significance level of 5%. Based on data analysis, a t-count value of 3,638 was obtained. The threshold value at degrees of freedom is 62 and the significance level is 1.670. Based on the results obtained, it can be concluded that there is an influence of the E-Module on students' understanding of concepts.